Pendekatan Struktural dalam Pembelajaran Bahasa Arab di Pondok Pesantren Nurul Huda Surabaya - Muhammad Tareh Aziz; Ummi Sholehawati; Mufarrohah; Hosnan (Program Studi Pendidikan Bahasa Arab Sekolah Tinggi Bahasa Arab dan Dakwah Masjid Agung Sunan Ampel Surabaya, 2023)
There are various assumptions about the Arabic language, including assumptions that consider Arabic as a habit, there are those who regard Arabic as a communication system that is basically spoken, and there are those who consider Arabic as a set of rules, norms and rules. The Structural Approach at Nurul Huda Islamic Boarding School is an approach to language learning which is based on the assumption that language is a rule. On the basis of this assumption arises the thought that language learning must prioritize mastery of language rules or grammar. Therefore, language learning needs to focus on knowledge of language structure which is included in phonology, morphology, and syntax. The approach in this study was to use a qualitative approach with an enthographic research type and the data collection method was to conduct direct interviews in the field with one of the administrators of the Nurul Huda Islamic Boarding School Foundation. The learning of Arabic at the Nurul Huda Islamic Boarding School can be divided into two parts, namely (1) Learning Arabic Grammar (Nahwu and Sharaf) and (2) Learning Arabic Muhadatsah. In learning Arabic grammar at Islamic boarding schools, it is intended for students who have already received education in junior high and high school because at this age the students are well-established to read, recite and translate Arabic.